Probabilistic planning for ligament-balanced TKA—Identification of critical ligament properties - Bartsoen, Laura; Faes, Matthias G. R.; Wirix-Speetjens, Roel; Moens, David; Jonkers, Ilse; Sloten, Jos Vander (Frontiers in Bioengineering and Biotechnology, 2022)
Total knee arthroplasty (TKA) failures are often attributed to unbalanced knee ligament loading. The current study aims to develop a probabilistic planning process to optimize implant component positioning that achieves a ligament-balanced TKA. This planning process accounts for both subject-specific uncertainty, in terms of ligament material properties and attachment sites, and surgical precision related to the TKA-process typically used in clinical practice. The consequent uncertainty in the implant position parameters is quantified by means of a surrogate model in combination with a Monte Carlo simulation. The samples for the Monte Carlo simulation are generated through a Bayesian parameter estimation on the native knee model in such a way that each sample is physiologically relevant. In this way, a subject-specific uncertainty is accounted for. A sensitivity analysis, using the Delta-moment independent sensitivity measure, is performed to identify the most critical ligament parameters. The designed process is capable of estimating the precision with which the targeted ligament-balanced TKA can be realized, and convert this in a success probability. This study shows that without additional subject-specific information (e.g. knee kinematic measurements), a global success probability of only 12 % is estimated. Furthermore, accurate measurement of reference strains and attachment sites critically improves the success probability of the pre-operative planning process. To allow more precise planning, a more accurate identification of these ligament properties is required. This study underlines the relevance of investigating in vivo or intra-operative measurement techniques to minimize uncertainty in ligament balanced pre-operative planning results, particularly prioritizing measurement of ligament reference strains and attachment sites.